2015
DOI: 10.1016/j.lungcan.2015.10.008
|View full text |Cite
|
Sign up to set email alerts
|

Phase 1 study of romidepsin plus erlotinib in advanced non-small cell lung cancer

Abstract: Purpose Preclinical studies demonstrated anti-tumor efficacy of the combination of the histone deacetylase (HDAC) inhibitor romidepsin plus erlotinib in non-small cell lung cancer (NSCLC) models that were insensitive to erlotinib monotherapy. We therefore, studied this combination in a phase 1 clinical trial in previously treated advanced NSCLC. Methods Romidepsin (8 or 10 mg/m2) was administered intravenously on days 1, 8, and 15 every 28 days in combination with erlotinib (150 mg orally daily), with romide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(16 citation statements)
references
References 43 publications
1
14
1
Order By: Relevance
“…Previous findings showed that no appetite is a predicter of weight loss and consequent nutritional risk or malnutrition in adults and older patients . This is in line with findings from 2 recent studies conducted in Japan, which showed that no appetite was the most prevalent symptom in patients with cancer, with a prevalence ranging from 20% to 24.4% . However, in 2 other studies conducted in patients with advanced cancer, the prevalence of no appetite varied between 53% and 57%, which is even higher than that found in our study …”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Previous findings showed that no appetite is a predicter of weight loss and consequent nutritional risk or malnutrition in adults and older patients . This is in line with findings from 2 recent studies conducted in Japan, which showed that no appetite was the most prevalent symptom in patients with cancer, with a prevalence ranging from 20% to 24.4% . However, in 2 other studies conducted in patients with advanced cancer, the prevalence of no appetite varied between 53% and 57%, which is even higher than that found in our study …”
Section: Discussionsupporting
confidence: 91%
“…34 This is in line with findings from 2 recent studies conducted in Japan, which showed that no appetite was the most prevalent symptom in patients with cancer, with a prevalence ranging from 20% to 24.4%. 35,36 However, in 2 other studies conducted in patients with advanced cancer, the prevalence of no appetite varied between 53% and 57%, which is even higher than that found in our study. [37][38][39] Nausea was higher in patients with gynecological cancer, and similar findings were reported in a conductive study at Aga Khan University Hospital, Pakistani, where 1 of the most common adverse effects was nausea (33.3%) in patients who received pelvic radiotherapy for gynecological cancer.…”
Section: Discussioncontrasting
confidence: 83%
“…These topoisomerase II inhibitors or DNA damage reagents could gain accessibility to target DNA thus increasing the efficacy since TMU‐35435 induces open chromatin structure. In addition, it warrants further investigation whether TMU‐35435 alone or in combination with other drugs could be used for overcoming the acquired resistance seen in most NSCLC patients who initially respond to EGFR TKI therapy or chemotherapy . It is likely that combined epigenetic therapy could result in increased antitumor activity in comparison to the use of single‐agent inhibitor of DNMTs or HDACs, but this needs validation in randomized studies.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the addition of an HDAC inhibitor (such as SAHA and SNDX‐275) to erlotinib or SAHA combined with gefitinib has become a novel clinical strategy to treat EGFR‐TKI resistance in patients suffering from NSCLC (NCT00503971, NCT00750698 and NCT02151721; https://www.clinicaltrials.gov/; accessed: April 11, 2017). The combination of romidepsin and erlotinib also exhibited inhibitory effects on relevant molecular targets in an unselected advanced NSCLC phase 1 clinical trial (Gerber et al, ). These findngs have led to the notion that HDAC inhibitors are promising drugs to potentiate the therapeutic efficacy of EGFR‐TKIs.…”
Section: Discussionmentioning
confidence: 99%